Pengaruh Rhizobakteria untuk Memacu Pertumbuhan dan Ketahanan Tanaman Kacang Tanah (Arachis hypogaea L.) terhadap Penyakit Bercak serta Karat Daun - PANDE MADE GIOPANY; I MADE SUDANA; TRISNA AGUNG PHABIOLA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
The Effects of Rhizobacteria to Promote the Growth and Peanut Resistance (Arachis hypogaea L.) Against Leaf Spot and Rust DiseasesPeanut (Arachis hypogaea L.) is an important legume plants that produces seeds with high protein and vegetable fat content, as well as many processed into various food products and as a source of vegetable oil. The purpose of this research is to know the effect of rhizobacteria to promote the growth and resistance of the peanut against diseases. The research used a Randomized Completely Block Design with 5 treatments and 5 replicates. The variables observed were plant height, number of branches, number of leaves, content of leaf chlorophyll, number of root nodules, disease intensity, disease intensity suppression, number of pods per plant, weight of pods per plant, dry weight of seeds per plant, dry weight of seeds per harvested area, and peanut yields per hectare. The results showed that all treatments of rhizobacteria used was able to promote the growth and resistance of the peanut against diseases so that peanut yields could be improved. Rhizobacteria RZ 35 and RZ 36 are rhizobacteria that have the best ability than other rhizobacterias. RZ 35 has more ability in improving growth and peanut resistance against diseases, whereas RZ 36 has more ability in improving peanut yields.